The cerebral microvasculature: Basic and clinical perspectives on stroke and glioma. (22nd November 2020) - Hoque, Maruf M.; Abdelazim, Hanaa; Jenkins‐Houk, Clifton; Wright, Dawn; Patel, Biraj M.; Chappell, John C.
Abstract: Microvascular networks are vital components of the cardiovascular system, performing many key roles in maintaining the health and homeostasis of the tissues and organs in which they develop. As discussed in this review, the molecular and cellular components within the microcirculation orchestrate critical processes to establish functional capillary beds, including organization of endothelial cell (EC) polarity, guiding investment of vascular pericytes (PCs), and building the specialized extracellular matrix (ECM) that comprises the vascular basement membrane (vBM). Herein, we further discuss the unique features of the microvasculature in the central nervous system (CNS), focusing on the cells contributing to the neurovascular unit (NVU) that form and maintain the blood‐brain barrier (BBB). With a focus on vascular PCs, we offer basic and clinical perspectives on neurovascular‐related pathologies that involve defects within the cerebral microvasculature. Specifically, we present microvascular anomalies associated with glioblastoma multiforme (GBM) including defects in vascular‐immune cell interactions and associated clinical therapies targeting microvessels (ie, vascular‐disrupting/anti‐angiogenic agents and focused ultrasound). We also discuss the involvement of the microcirculation in stroke responses and potential therapeutic approaches. Our goal was to compare the cellular and molecular changes that occur in the microvasculature and NVU, and to provide a commentary on factors driving disease progression in GBM and stroke. We conclude with a forward‐looking perspective on the importance of microcirculation research in developing clinical treatments for these devastating conditions.